Trends in Hospitalization Rates and Outcomes of Endocarditis among Medicare Beneficiaries - Bikdeli, Behnood (J Am Coll Cardiol, 2013)
OBJECTIVES: To determine the hospitalization rates and outcomes of endocarditis among older adults. BACKGROUND: Endocarditis is the most serious cardiovascular infection and is especially common among older adults. Little is known about recent trends for endocarditis hospitalizations and outcomes. METHODS: Using Medicare inpatient Standard Analytic Files, we identified all Fee-For-Service beneficiaries aged ≥65 years with a principal or secondary diagnosis of endocarditis from 1999-2010. We used Medicare Denominator Files to report hospitalizations per 100,000 person-years. Rates of 30-day and 1-year mortality were calculated using Vital Status Files. We used mixed-effects models to calculate adjusted rates of hospitalization and mortality and to compare the results before and after 2007, when the American Heart Association revised recommendations for endocarditis prophylaxis. RESULTS: Overall, 262,658 beneficiaries were hospitalized with endocarditis. The adjusted hospitalization rate increased from 1999-2005, reaching 83.5 per 100,000 person-years in 2005, and declined during 2006-2007. After 2007, the decline continued, reaching 70.6 per 100,000 person-years in 2010. Adjusted 30-day and 1-year mortality rates ranged from 14.2% to 16.5% and from 32.6% to 36.2%, respectively. There were no consistent changes in adjusted rates of 30-day and 1-year mortality after 2007. Trends in rates of hospitalization and outcomes were consistent across demographic subgroups. Adjusted rates of hospitalization and mortality declined consistently in the subgroup with principal diagnosis of endocarditis. CONCLUSIONS: Our study highlights the high burden of endocarditis among older adults. We did not observe an increase in adjusted rates of hospitalization or mortality associated with endocarditis after publication of the 2007 guidelines.